Mechanisms involved in the adaptation of Escherichia coli O157:H7 to the host intestinal microenvironment. Issue 24 (23rd December 2020) - Fernandez-Brando, Romina J.; McAteer, Sean P.; Montañez-Culma, Johanna; Cortés-Araya, Yennifer; Tree, Jai; Bernal, Alan; Fuentes, Federico; Fitzgerald, Stephen; Pineda, Gonzalo E.; Ramos, M. Victoria; Gally, David L.; Palermo, Marina S.
Abstract: Host adaptation of pathogens may increase intra- and interspecies transmission. We showed previously that the passage of a clinically isolated enterohemorrhagic Escherichia coli (EHEC) O157 strain (125/99) through the gastrointestinal tract of mice increases its pathogenicity in the same host. In this work, we aimed to elucidate the underlying mechanism(s) involved in the patho-adaptation of the stool-recovered (125RR) strain. We assessed the global transcription profile by microarray and found almost 100 differentially expressed genes in 125RR strain compared with 125/99 strain. We detected an overexpression of Type Three Secretion System (TTSS) proteins at the mRNA and protein levels and demonstrated increased adhesion to epithelial cell lines for the 125RR strain. Additional key attributes of the 125RR strain were: increased motility on semisolid agar, which correlated with an increased fliC mRNA level; reduced Stx2 production at the mRNA and protein levels; increased survival at pH 2.5, as determined by acid resistance assays. We tested whether the overexpression of the LEE-encoded regulator ( ler ) in trans in the 125/99 strain could recreate the increased pathogenicity observed in the 125RR strain. As anticipated ler overexpression led to increased expression of TTSS proteins and bacterial adhesion to epithelial cells in vitro but also increased mortality and intestinal colonization in vivo . We conclude that this host-adaptation process required changes in several mechanisms that improved EHEC O157 fitness in the new host. The research highlights some of the bacterial mechanisms required for horizontal transmission of these zoonotic pathogens between their animal and human populations.